High‐Quality Cs2AgBiBr6 Double Perovskite Film for Lead‐Free Inverted Planar Heterojunction Solar Cells with 2.2 % Efficiency. Issue 14 (3rd May 2018) - Gao, Weiyin; Ran, Chenxin; Xi, Jun; Jiao, Bo; Zhang, Wenwen; Wu, Mincai; Hou, Xun; Wu, Zhaoxin
Abstract: All‐inorganic double‐metal perovskite materials have recently gained much attention due to their three dimensionality (3D) and non‐toxic nature to replace lead‐based perovskite materials. Among all those double perovskite materials, theoretical works have demonstrated that Cs2 AgBiBr6 shows high stability and possesses a suitable band gap for solar‐cell applications. However, the film‐forming ability of Cs2 AgBiBr6 is found to be the utmost challenge hindering its development in thin‐film solar‐cell devices. In this work, a high‐quality Cs2 AgBiBr6 film with ultra‐smooth morphology, micro‐sized grains, and high crystallinity is realized via anti‐solvent dropping technology and post‐annealing at high temperature. After optimization, the first example of an inverted planar heterojunction solar‐cell device based on Cs2 AgBiBr6 exhibits a power conversion efficiency of 2.23 % with V OC =1.01 V, J SC =3.19 mA/cm 2, and FF=69.2 %. Besides, the device shows no hysteresis and a high stability. Abstract : A high‐quality double perovskite film is prepared by fast crystallization via the anti‐solvent dropping method. Micro‐sized grains and a high crystallinity of the film can be obtained by a post‐annealing process. The resulting inverted planar heterojunction solar‐cell devices show a decent efficiency of 2.23% with no hysteresis and a high stability.